ANALISIS KOMPARATIF KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS PADA PT CHAMPION PACIFIC INDONESIA TBK DAN PT IMPACK PRATAMA INDUSTRI TBK - Winiarti, Iin; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to compare the financial performance of PT Champion Pacific Indonesia Tbk and PT Impack Pratama Industri Tbk based on liquidity, solvency, and profitability ratios. The method used is quantitative descriptive with secondary data from the companies' annual financial statements. The analysis was conducted through financial ratio calculations, normality tests, and the Mann-Whitney test. The results show that PT Champion Pacific Indonesia Tbk is superior in terms of liquidity and solvency, while PT Impack Pratama Industri Tbk is superior in profitability. However, statistically, the Mann-Whitney test proves that a significant difference only exists in the liquidity ratio (Current Ratio), while no significant differences are found in solvency and profitability between the two companies.